Factors affecting modern contraceptive use among fecund young women in Bangladesh: does couples' joint participation in household decision making matter? - Ahmed Zohirul Islam (BMC, 2018)
Abstract Objectives The purpose of the study was to explore the association between couples' joint participation in household decision making and modern contraceptive use (MCU) among fecund (physically able to bear child) young women in Bangladesh. Methods This study utilized a cross-sectional data (n = 3507) extracted from the Bangladesh Demographic and Health Survey (BDHS) 2011. Differences in the utilization of modern contraceptives (MC) by socio-demographic characteristics were assessed by χ2 analyses. Binary logistic regression was used to identify the associated factors of usingMC, and the odds ratio with a 95% CI was computed to assess the strength of association. Multicollinearity was also checked by examining the standard errors in the fitted model. Results Desire for a child after two years go by and no child at all contributed the most to increasing MCU followed by receiving family planning (FP) methods from FP workers. Couples' joint decision making power on women's health care, child's health care and visiting family members or relatives emerged as the third most influential factor that might be associated with MCU. Conclusions Since spousal joint decision making increases the likelihood of using MC, government should include strategic interventions in FP programs to elevate women's status through creating educational and employment opportunities and encouraging more visible involvement in household decision making.